Performance analysis and optimization of cooperative spectrum sensing with relay - Mei-ling LI (Tongxin xuebao, 2013)
An object based cooperative spectrum sensing scheme with relay was proposed,and the fact that the channel condition from SU to SR has an important influence to system performance was proved.In view of this,an optimized cooperative spectrum sensing scheme with best relay(optimized BRCSS) was proposed,in which the best secondary relay was selected by considering both the channel condition from SU to SR and SR to FC.Finally,an adaptive cooperative spectrum sensing scheme with best relay (A-BRCSS) was proposed further to save the system expense considering more practical application occasion,where,SU could adaptively decide whether the relay’s cooperation was needed by its reporting channel condition.Both analysis and simulation results show that,the better sensing performance can be achieved by the optimized BRCSS scheme compared with the tradit l cooperative spectrum sensing scheme with best relay.The nearly best sensing performance can be obtained by the proposed A-BRCSS scheme.